Liquid-phase alkylation of phenol with long-chain olefins over WOx/ZrO2 solid acid catalysts - Sarish, S.; Devassy, Biju M.; Bohringer, Walter; Fletcher, Jack C. Q.; Halligudi, Shivaraj B. (Journal of Molecular Catalysis A-Chemical, 2005)
The liquid-phase alkylation of phenol with 1-dodecene was carried out over WOx/ZrO2 solid acid catalysts. The catalysts were prepared by wet impregnation method using zirconium oxyhydroxide and ammonium metatungstate. Catalysts with different WO3 loading (5-30 wt.%) were prepared and calcined at 800 degrees C and catalyst with 15% WO3 was calcined from 700-850 degrees C. All the catalysts were characterized by surface area, XRD, and FTIR. The catalyst with 15% WO3 calcined at 800 degrees C (15 WZ-800) was found to be the most active in the reaction. The effect of temperature, molar ratio and catalyst weight on dodecene conversion and products selectivity was studied in detail. Under the optimized reaction conditions of 120 degrees C, phenol/1-dodecene molar ratio 2 and time 2 h, the catalyst 15 WZ-800 gave > 99% dodecene conversion with 90% dodecylphenol selectivity. Comparison of the catalytic activity of 15 WZ-800 with sulfated zirconia calcined at 500 degrees C (SZ-500) and HP zeolite showed that activity of SZ-500 was lower than that of 15 WZ-800, while HP zeolite showed negligible activity. It is observed that the presence of water in the reaction mixture was detrimental to the catalytic activity of WOx/ZrO2. The catalyst 15 WZ-800 also found to be an efficient catalyst for alkylation of phenol with long-chain olefins like 1-octene and 1-decene. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: Alkylation; long-chain olefins; phenol; tungsten oxide; Zirconia

Silicotungstate-modified zirconia as an efficient catalyst for phenol tert-butylation - Devassy, Biju M.; Shanbhag, G. V.; Mirajkar, Subhash P.; Bohringer, Walter; Fletcher, Jack C. Q.; Halligudi, Shivaraj B. (Journal of Molecular Catalysis A-Chemical, 2005)
The alkylation of phenol with tert-butanol was investigated using zirconia modified with silicotungstic acid (STA) as catalysts. The catalysts with different STA loading (5-25 wt.% calcined at 750 degrees C) and calcination temperature (15 wt.% calcined from 350 to 850 degrees C) were prepared and characterized by X-ray diffraction and NH3-TPD measurements. The XRD results indicate that STA stabilizes the tetragonal phase of zirconia. The catalyst with 15% STA on ZrO2 calcined at 750 degrees C shows the highest acidity and hence highest activity. Under the reaction conditions of 140 degrees C, tert-butanol/phenol molar ratio of 2 and LHSV of 4 h(-1), phenol conversion was 95.4% with selectivity to 2-tert-butyl phenol 4.3%, 4-tert-butyl phenol 59.2% and 2,4-di-tert-butyl phenol 35.8%. The reaction was studied as a function of time for 50 It without appreciable change in phenol conversion and product selectivity. The deactivated catalyst could be regenerated by calcination with out appreciable lose in catalytic activity and product selectivity. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: phenol; Silicotungstic acid; tert-butylation; Zirconia

Synthesis of linear alkyl benzenes over zirconia-supported 12-molybdophosphoric acid catalysts - Devassy, Biju M.; Lefebvre, F.; Bohringer, Walter; Fletcher, Jack C. Q.; Halligudi, Shivaraj B. (Journal of Molecular Catalysis A - Chemical, 2005)
The liquid-phase alkylation of benzene with 1-octene and 1-dodecene was investigated using zirconia-supported 12-molybdophosphoric acid (MPA) as catalyst. The catalysts with different MPA loading (5-25 wt.% calcined at 700 degrees C) and calcination temperature (15 wt.% calcined from 500 to 750 degrees C) were prepared by suspending zirconium oxyhydroxide in methanol solution of MPA followed by drying and calcination. These catalysts were characterized by X-ray diffraction, and P-31 MAS NMR spectroscopy measurements. The XRD results indicated that MPA stabilizes the tetragonal phase of zirconia. 3 1 P MAS NMR spectra show that the nature of phosphorous species depend on MPA loading and calcination temperature, and it show the existence of three types of phosphorous species, one is the Keggin unit and the other is the decomposition product of MPA and third one an unidentified species. FTIR pyridine adsorption on 15% MPA catalyst calcined at 700 degrees C showed the presence both Bronsted and Lewis acidity. Under the reaction conditions of 83 C, benzene/1-olefin molar ratio of 10 (time, 1 h), the most active catalyst, 15% MPA calcined at 700 C gave more than 90% olefin conversion with selectivity to 2-phenyl octane, 55% and 2-phenyl dodecane, 45%. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: 12-molybdophosphoric acid; benzene alkylation; linear alkyl benzene; Zirconia

tert-Butylation of p-cresol over WOx/ZrO2 solid acid catalysts - Sarish, S.; Devassy, Biju M.; Halligudi, Shivaraj B. (Journal of Molecular Catalysis A - Chemical, 2005)
The tert-butylation of p-cresol with tert-butanol was carried out over WO3/ZrO2 catalysts under flow conditions, The catalysts were prepared by wet impregnation method using zirconium oxyhydroxide and ammonium metatungstate. Catalysts with different WO3 loading (5-30 wt.%) were prepared and calcined at 800 degrees C and catalyst with 15% WO,, was calcined from 600 to 900 C. The catalysts were characterized by surface area, XRD, FTIR and TEM. The catalyst 15% WO3/ZrO2 calcined at 800 degrees C found to be the most active in the reaction. The effect of temperature, space velocity and molar ratio of the reactants on the conversion of p-cresol and products selectivities were studied. Under the optimized reaction conditions of 130 degrees C, tert-butanol/p-cresol molar ratio of 3 and flow rate of 10 ml h(-1). p-cresol conversion was 69.8% with selectivity to 2-tert-butyl-p-cresol 92.4%, 2,6-di-tert-butyl-p-cresol 6.3% and p-cresol tert-butyl ether 1.3%. The catalytic activity is compared with sulfated zirconia, USY, H beta zeolites and montmorillonite K-10 under the optimized reaction conditions The activity of sulfated zirconia is lower than that of 15% WO3/ZrO2 catalyst calcined at 800 C and other catalysts showed very low activity, (c) 2005 Elsevier B.V.. All rights reserved.
Keywords: p-Cresol; tert-butylation; tungsten oxide; Zirconia

Zirconia-supported 12-tungstophosphoric acid as a solid catalyst for the synthesis of linear alkyl benzenes - Devassy, Biju M.; Lefebvre, F.; Halligudi, Shivaraj B. (Journal of Catalysis, 2005)
The liquid-phase alkylation of benzene with 1-octene and 1-dodecene was investigated with zirconia-supported 12-tungstophosphoric acid (TPA) as catalysts. We prepared the catalysts, with different TPA loading (5-20 wt% calcined at 750 degrees C) and calcination temperatures (15 wt% calcined from 650 to 850 degrees C), by suspending hydrous zirconia in a methanol solution of TPA, followed by drying and calcination. These catalysts were characterized by X-ray diffraction, DTG-DTA, FTIR pyridine adsorption, NH3-TPD, and P-31, MAS NMR spectroscopy measurements. The catalyst with optimum TPA loading (15%) and calcination temperature (750 degrees C) was prepared in different solvents and characterized by P-31 MAS NMR spectroscopy. The XRD results indicate that TPA stabilizes the tetragonal phase of zirconia. The catalysts show both Bronsted and Lewis acidity, and 15% TPA on zirconia calcined at 750 degrees C shows the highest acidity. P-31 MAS NMR spectra show two types of phosphorous species: one is the Keggin unit and the other is the decomposition product of TPA. The relative amount of each depends on TPA loading, calcination temperature, and the solvent used for the catalyst preparation. Under reaction conditions of 84 degrees C and a benzene/1-olefin molar ratio of 10 (time 1 h), the most active catalyst, 15% TPA, calcined at 750 degrees C, gave more than 98% olefin conversion with selectivity for 2-phenyl octane (53.5%) and 2-phenyl dodecane (47%). (c) 2004 Elsevier Inc. All rights reserved.
Keywords: 12-tungstophosphoric acid; linear alkyl benzene; solvent effect; Zirconia

Zirconia-supported phosphotungstic acid as catalyst for alkylation of phenol with benzyl alcohol - Devassy, Biju M.; Shanbhag, G. V.; Lefebvre, F.; Bohringer, Walter; Fletcher, Jack C. Q.; Halligudi, Shivaraj B. (Journal of Molecular Catalysis A - Chemical, 2005)
The liquid-phase alkylation of phenol with benzyl alcohol was carried out using zirconia-supported phosphotungstic acid (PTA) as catalyst. The catalysts with different PTA loadings (5-20 wt.% calcined at 750 degrees C) and calcination temperature (15 wt.% calcined from 650 to 850 degrees C) were prepared and characterized by (31)p MAS NMR and FT-IR pyridine adsorption spectroscopy. The catalyst with optimum PTA loading (15%) and calcination temperature (750 degrees C) was prepared in different solvents. 31p MAS NMR spectra of the catalysts showed two types of phosphorous species, one is the Keggin unit and the other is the decomposition product of PTA and the relative amount of each depends on PTA loading, calcination temperature and the solvent used for the catalyst preparation. The catalysts with 15% PTA on zirconia calcined at 750 degrees C showed the highest Bronsted acidity. At 130 degrees C and phenol/benzyl alcohol molar ratio of 2 (time, I h), the most active catalyst, 15% PTA calcined at 750 degrees C gave 98% benzyl alcohol conversion with 83% benzyl phenol selectivity. (c) 2004 Elsevier B.V. All rights reserved.
Keywords: Benzylation; phenol; Phosphotungstic acid; Zirconia

Effect of calcination temperature on the catalytic activity of zirconia-supported heteropoly acids - Devassy, Biju M.; Halligudi, Shivaraj B. (Journal of Molecular Catalysis A-Chemical, 2006)
Zirconia-supported silicotungstic acid (15% STA) catalyst with different calcination temperatures (600-850 degrees C) was prepared by suspending zirconium oxyhydroxide in methanol solution of STA followed by drying and calcination. These catalysts were characterized by XRD, FTIR pyridine adsorption and DRUV-vis spectroscopy. The catalysts showed both Bronsted as well as Lewis acidity and 15% STA on zirconia calcined at 750 degrees C (15 SZ-750) had the highest Bronsted acidity. Characterization of 15 SZ-750 catalyst by Raman spectroscopy showed the presence of zirconia-anchored mono-oxotungstate as the major tungsten species present in this catalyst. These catalysts were used in benzoylation of veratrole with benzoic anhydride and 15 SZ-750 catalyst showed the highest activity. For catalyst with support calcined at different temperatures before HPA impregnation, catalytic activity decreases as the support calcination temperature increases due to the decrease in Bronsted acidity. Comparison of the catalytic activity of 15 SZ-750 with that of zirconia-supported phosphotungstic acid (15%, calcined at 750 degrees C, 15 PZ-750) in benzoylation of veratrole with benzoic anhydride, acylation of anisole with acetic anhydride and in alkylation of diphenylether with 1-dodecene showed that 15 SZ-750 catalyst has higher activity and deactivation resistance due to its higher Bronsted acidity. The deactivated catalyst could be regenerated by calcination without appreciable loss in activity. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: Acylation; Alkylation; Anisole; diphenylether; Phosphotungstic acid; Silicotungstic acid; veratrole; Zirconia

Phenol tert-butylation over zirconia-supported 12-molybdophosphoric acid catalyst - Devassy, Biju M.; Shanbhag, G.V.; Halligudi, S.B. (Journal of Molecular Catalysis A-Chemical, 2006)
The alkylation of phenol with tert-butanol was investigated using zirconia-supported 12-molybdophosphoric acid (MPA) as catalyst. The catalysts with different MPA loading (5-25 wt.% calcined at 700 degrees C) and calcination temperature (15 wt.% calcined from 500 to 750 degrees C) were prepared by suspending zirconium oxyhydroxide in methanol solution of MPA followed by drying and calcination. These catalysts were characterized by X-ray diffraction and (31)p MAS NMR spectroscopy measurements. The XRD results indicated that MPA stabilizes the tetragonal phase of zirconia. (31)p MAS NMR spectra showed the presence of three types of phosphorous species, phosphomolybdate in interaction with zirconia, decomposition product of MFPA and an unidentified species. IFTIR pyridine adsorption on 15% MPA catalyst calcined at different temperatures showed the presence of both Bronsted and Lewis acidity and the catalyst calcined at 700 degrees C showed the highest relative Bronsted acidity. Under the reaction conditions of 140 degrees C, tert-butanol/phenol molar ratio of 2 and LHSV of 4 h(-1), the phenol conversion was 80.6% at 2 h (selectivity to 2-TBP 11.5%, 2,4-DTBP 55.2%, and 4-TBP 25.7%), which decreased slowly with time and at 31 h, it was 58.5% (selectivity to 2-TBP 15.2%, 2,4-DTBP 41.6%, and 4-TBP 38.4%). The major reason for the catalyst deactivation was the reduction and leaching of MPA from the catalyst surface. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: 12-molybdophosphoric acid; phenol; tert-butylation; Zirconia

Highly efficient and chemo selective catalyst system for the synthesis of blossom orange fragrance and flavoring compounds - Justus, Josena; Vinu, Ajayan; Devassy, Biju M.; Balasubramanian, Veerappan V.; Bohringer, Walter; Fletcher, Jack C. Q.; Halligudi, Shivaraj B. (Catalysis Communications, 2008)
{Acetal and acylal formation reactions of organic compounds are efficiently catalyzed by zirconia-supported mixed oxide systems under liquid-phase reaction conditions. 15WZ-750 (where
Keywords: Acetal; acylal; Silicotungstic acid; tungsten oxide; tungstophosphoric acid; Zirconia

Synthesis of biodiesel over zirconia-supported isopoly and heteropoly tungstate catalysts - Sunita, G.; Devassy, Biju M.; Vinu, Ajayan; Sawant, Dhanashri P.; Balasubramanian, Veerappan V.; Halligudi, Shivappa B. (Catalysis Communications, 2008)
The liquid-phase synthesis of biodiesel by transesterification of sunflower oil with methanol is carried out by using zirconia-supported isopoly and heteropoly tungstates (HPAs) as catalysts. The isopoly and heteropoly tungstate catalysts were prepared by suspending zirconium oxyhydroxide in water/methanol solution of ammonium metatungstate/silicotungstic acid, phosphotungstic acid (WO3/HPA loading, 15%,,) followed by drying and calcination at 750 degrees C. The catalysts were characterized by XRD, Raman spectroscopy, IR spectroscopy, NH3-TPD and FTIR pyridine adsorption spectroscopy. XRD results indicate that the presence of isopoly and heteropoly tungstates stabilizes ZrO2 in tetragonal phase. Raman and IR spectra of the catalysts show that tungstate species exist as zirconia-anchored octahedral mono-oxotungstate. The acidity measurements by NH3-TPD and FTIR pyridine adsorption spectroscopy show that zirconia-supported phosphotungstate has the highest total acidity and zirconia-supported isopoly tungstate has the highest Bronsted acidity. The zirconia-supported isopoly tungstate shows superior catalytic performance compared to zirconia-supported heteropoly tungstate catalysts. Under the reaction conditions of 200 degrees C and methanol/oil molar ratio 15, 15% WO3/ZrO2 calcined at 750 degrees C gave 97% conversion of oil. This catalyst also efficiently catalyzes methanolysis of other vegetable oils like mustard oil and sesame oil. The deactivated catalyst could be regenerated by calcination without appreciable loss in activity. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: Biodiesel; phosphotungstic acids; Silicotungstic acid; transesterification; tungsten oxide; Zirconia